Inaction as Nonformal Reaction: Rethinking Crime Perception in the Era of Data Breaches - Hadi, Irnasya Shafira (UI Scholars Hub, 2025)
This study analyses the Indonesian public’s response to government data breaches and advocates for an expanded defintion of nonformal reactions to crime in the digital context. It argues that existing criminological frameworks, particularly Mustofa’s (2021) model—which views nonformal reactions as active and confrontational behaviours such as demonstrations or vigilantism—should also acknowledge inaction, apathy, and emotional disengagement as valid public reactions. This paper employs a conceptual-qualitative approach, combining an interdisciplinary literature review, interpretive policy analysis of the Personal Data Protection Law, and triangulation with digital behaviour data to develop its analysis. This paper reframes apathy as a significant criminological indicator of institutional breakdown and democratic erosion, rather than a mere absence of action. By incorporating passive reactions into the notion of nonformal reactions to crime, this research enhances the analytical framework for Indonesian criminology in the context of cybercrime victimisation. Recognising inaction as a form of reaction is crucial for assessing civic trust, ensuring state accountability, and advancing a secure digital culture. The study advocates for an evolution of criminological theory to maintain its relevance in the changing landscape of harm within a hyper-connected society.